Current principles for the planning and performance of radiotherapy in the conservative treatment of locally advanced cancer of the cervix uteri - Yu. M. Kreynina; V. A. Titova; T. F. Scobeleva (ABV-press, 2014)
The paper analyzes the strategy and tactics of beam and intracavitary radiation within the framework of chemoradiotherapy in 112 pa- tients with inoperable FIGO stages IIa-IIIb cancer of the cervix uteri. The parameters that are important to plan general radiotherapy stages are assessed; the bases for optimization decisions and the specific features of maintenance therapy, which ensure a 15-25 % increase in the efficiency of treatment with its satisfactory tolerability, are given.